Parental recovered acute kidney injury causes prenatal renal dysfunction and fetal growth restriction with sexually dimorphic implications for adult offspring - Hebert, Jessica F.; Funahashi, Yoshio; Emathinger, Jacqueline M.; Nickerson, Megan N.; Groat, Tahnee; Andeen, Nicole K.; Gurley, Susan B.; Hutchens, Michael P. (Frontiers in Physiology, 2024)
Introduction: Acute kidney injury (AKI) is rapidly increasing in global incidence and a healthcare burden. Prior maternal AKI diagnosis correlates with later pregnancy complications. As pregnancy influences developmental programming, we hypothesized that recovered parental AKI results in poor pregnancy outcomes, impaired fetal growth, and adult offspring disease. Methods: Using a well-characterized model of rhabdomyolysis-induced acute kidney injury (RIAKI), a form of AKI commonly observed in young people, we confirmed functional renal recovery by assessing glomerular filtration rate (GFR) 2 weeks following RIAKI. We bred sham and recovered RIAKI sires and dams in timed, matched matings for gestational day (GD) 16.5 and offspring (birth–12 weeks, 6 months) study. Results: Despite a normal GFR pre-pregnancy, recovered RIAKI dams at GD16.5 had impaired renal function, resulting in reduced fetoplacental ratios and offspring survival. Pregnant RIAKI dams also had albuminuria and less renal megalin in the proximal tubule brush border than shams, with renal subcapsular fibrosis and higher diastolic blood pressure. Growth-restricted offspring had a reduced GFR as older adults, with evidence of metabolic inefficiency in male offspring; this correlated with reduced renal AngII levels in female offspring from recovered RIAKI pairings. However, the blood pressures of 6-month-old offspring were unaffected by parental RIAKI. Conclusions: Our mouse model demonstrated a causal relationship among RIAKI, gestational risk, and developmental programming of the adult-onset offspring GFR and metabolic dysregulation despite parental recovery.